Faculty of Information Management, UiTM : past, present and future / Associate Professor Dr. Adnan Jamaludin and Professor Dato' Dr. Raja Abdullah Yaacob - Jamaludin, Adnan; Yaacob, Raja Abdullah (Faculty of Information Management, 2009)
Technological developments and the birth of knowledge economy have opened up new avenues in the information profession, leading to emerging roles of the information professionals (IPs). At this critical juncture, new competencies are needed for the new breed of IPs, calling for active process of learning, relearning, and unlearning. The Faculty of Information Management has undergone such challenges since it was first established in 1968 and the development of the programmes continues to evolve. It would be interesting to unravel how the faculty came into being to become the most prominent information faculty in the region. The ongoing development of advanced technologies in libraries and information agencies has placed a high priority on ICT and knowledge competencies among library staff and IPs and the faculty will continue to move according to the needs of the market.